Unhappy Confessions: The Temptation of Admitting to White Privilege - Claire A Lockard (Feminist Philosophy Quarterly, 2016)
Admissions of white privilege and/or racism are common among white anti-racists and others who want to combat their racism. In this article, I argue that because such admissions are conscious attempts to address unconscious habits, they are unhappy speech acts and contrary to their implied aims. Admissions of white privilege or racism can be conceptualized as Foucauldian confessions that are pleasurable to enact but ultimately reinforce white people’s feelings of goodness and allow them to avoid addressing this racism. I ground my argument in Shannon Sullivan’s analysis of white privilege and Sara Ahmed’s critique of confessions of racism/privilege to show that in addition to doing no anti-racist work at the moment of saying, these confessions actually reify white privilege deeper into the unconscious and make it harder to address. Sullivan’s work, I conclude, offers white people a more productive way forward than their unhappy performative declarations of privilege. A white person’s understanding of her confessing habit cannot break this habit, but it might orient her toward examining what sorts of anti-racist moves do work.